Vocabulary Studies in First and Second Language Acquisition - Richards, Brian. author. aut Link
XIX, 248 p.
Keywords: International scholars and researchers present cutting edge contributions on the significance of vocabulary in current thinking on first and second language acquisition in the school and at home. By pursuing common themes across first and second language and bilingual contexts, the editors offer a collection that tackles the most important issues.